Hybrid Cultivar and Crop Protection to Support Winter Rye Yield in Continuous Cropping - Marta K. Kostrzewska; Magdalena Jastrzębska (Agriculture, 2025)
Continuous cropping (CC) of cereals leads to reduced yields due to cumulative biotic and abiotic stresses. Winter rye, Secale cereale L., is considered relatively CC-tolerant, yet it may still suffer under prolonged monocropping. This six-year study (2017–2022) aimed to assess the effects of cropping systems (CC vs. crop rotation, CR), cultivar type (hybrid vs. population), and chemical plant protection (control treatment, herbicide, herbicide plus fungicide) on winter rye yield and yield components. The study was conducted as part of a long-term field experiment in northeastern Poland that started in 1967. Two cultivars, KWS Binntto (hybrid) and Dańkowskie Diament (population), were evaluated across treatments. Overall, CR led to significantly higher yields and better performance of all yield components than CC. The hybrid cultivar consistently outperformed the population cultivar. Chemical plant protection improved yield under CC, but was redundant under CR. The hybrid cultivar cultivated in CC protected by rational chemical treatments produced equal or greater yields than the population cultivar grown in CR. In CC conditions, hybrid rye exhibited greater yield stability and resilience to interannual weather variation than the population cultivar. These findings support the use of hybrid rye with rational chemical protection as a practical strategy to sustain productivity in CC systems without relying solely on crop rotation.